Development of alternative force converter for electric generator uses - Ahmad Hafiz, Zainudin (2008)
In this thesis, the objective is to design a new concept of a prototype force converter, analyze the mechanism to manipulate the energy, and fabricate the prototype based on the approved mechanism design. Buoyancy force has been chosen based on better characteristic compare to conventional energy resource to be converted into torque to rotate the dynamo before the electricity can be generated. The only changed in this mechanism design is at air trap mechanism, this is the most important part to archive higher efficiency in producing electricity. Theoretically, within this design it can produce maximally 111 N.m torque. Based on the analysis toward this alternative force converter, net power output that can be generated by this machine is 450 W.